Turn-Taking in Colloquial Indonesian - Agus Subiyanto Subiyanto (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2017)
Participants in a conversation follow certain basic rules in obtaining turns. Some questions addressed in this paper are, firstly, how turns are allocated in Indonesian conversation. Secondly, what  are the signals given by a current speaker willing to yield to a next speaker (i.e. turn-yielding signals). Thirdly, what repair mechanism is  employed by the participants when the turn-taking procedures are broken. The data used in this study were taken from an informal conversation of four Indonesians from Jakarta. The data were collected by using a non-participatory observation with a recording technique. The analysis shows that the turn-taking system in the Indonesian language confirms the model of turn-taking system developed by Sacks et al (1974), covering the occurrence and the recurrence of speaker change, the overwhelming tendency for one party to talk at a time,the common occurrences of more than one speaker at a time, and the common switches of speakers with no gapsand no overlaps.